Central role of suppressors of cytokine signaling proteins in hepatic steatosis, insulin resistance, and the metabolic syndrome in the mouse - Ueki, Kohjiro (National Academy of Sciences, 2004)
Insulin resistance, obesity, diabetes, dyslipidemia, and nonalcoholic fatty liver are components of the metabolic syndrome, a disease complex that is increasing at epidemic rates in westernized countries. Although proinflammatory cytokines have been suggested to contribute to the development of these disorders, the molecular mechanism is poorly understood. Here we show that overexpression of suppressors of cytokine signaling (SOCS)-1 and SOCS-3 in liver causes insulin resistance and an increase in the key regulator of fatty acid synthesis in liver, sterol regulatory element-binding protein (SREBP)-1c. Conversely, inhibition of SOCS-1 and -3 in obese diabetic mice improves insulin sensitivity, normalizes the increased expression of SREBP-1c, and dramatically ameliorates hepatic steatosis and hypertriglyceridemia. In obese animals, increased SOCS proteins enhance SREBP-1c expression by antagonizing STAT3-mediated inhibition of SREBP-1c promoter activity. Thus, SOCS proteins play an important role in pathogenesis of the metabolic syndrome by concordantly modulating insulin signaling and cytokine signaling.